PENINGKATAN PROSES PENGAMBILAN KEPUTUSAN DALAM PEMILIHAN ALTERNATIF DESAIN KONSTRUKSI PROYEK JALAN TOL TINGGI UTARA STUDI KASUS PT XYZ - Nastiti Ramadhyanti; Utomo Sarjono Putro (LPPM STIE Muhammadiah Bandung, 2025)
This study addresses the inefficiency in the decision-making process of PT XYZ for selecting the basic design of the North Elevated Toll Road (NETR) project. Initially driven solely by cost considerations, the previous approach overlooked critical factors such as environmental impact, social implications, construction complexity, and land acquisition processes. Through the application of the Analytic Hierarchy Process (AHP) and Value Engineering (VE), this research proposes a more comprehensive decision-making model. Primary data were collected via in-depth questionnaires and focus group discussions involving key stakeholders within PT XYZ. The results highlight the importance of adopting a multi-criteria framework to avoid project delays, minimize risk, and improve long-term feasibility. By integrating financial and non-financial criteria, the study identifies the most suitable design alternative and proposes an implementation plan for its adoption. This model aims to support more accountable and strategic infrastructure decisions within PT XYZ and similar organizations in future projects.